EXPLORING THE CHALLENGES ON THE IMPLEMENTATION OF INCLUSIVE EDUCATION IN EARLY CHILDHOOD EDUCATION: A CASE OF CHILDREN WITH DISABILITIES - Athumani Juma Mgaya; Yohana Richard Gesase (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
Particularly the study explored if the absence of trained and qualified teachers in early childhood, stigma on students with disabilities, unsuitable infrastructures, and improper methodologies for instruction and curriculum were features that obstruct the stipulation of special needs education in preschool. The study was carried out in 10 preschools, which were randomly selected in Morogoro Municipality involving teachers and heads of preschools. The descriptive design was employed while using a mixed method to analyze the variables and more interpretation whereby instruments employed were questionnaires and interviews. Statistical analysis was employed using ANOVA and Chi-square with p-value ≤ .05 and CL of 0.95 with the support of percentages, tables, and charts. Participation and self-esteem, motivation, benefits as well as the type of disability seem to greatly influence the accomplishment of inclusive education. On the other side insufficient teacher training, deficient materials for learning and teaching, and unsuitable curriculum were observed to slow down the execution of inclusive education. Results of this study showed that there is an unfavorable environment for learning, and the minimum point of understanding and knowledge on content about special needs education among teachers. It is expected that these findings will help and support the Ministry of Education to design, manage, and administer inclusive education in early childhood education adequately and in a proper manner.